Obtenção e caracterização de espumas vítreas a partir de resíduos de lâmpadas fluorescentes descontaminados de mercúrio - Nunes, Isaac dos Santos (My University, 2015)
Glass foams are heterophasic materials applied in acoustic and thermal insulation, and compared to other materials, are lightweight and sturdy. Glass foams can be prepared from glass packaging, cathode ray tubes and other wastes like fly ashes. Waste fluorescent lamps, classified according the NBR 10.004-04 as hazardous due to the presence of mercury, have potential characteristics for use in the obtainment of glass foams. Decontamination of such residues makes their sending to controlled landfills possible, however it is necessary to development of processes that address the use of these materials in economic interest products, considering environmental issues. Therefore, this work aims to prepare ceramic bodies from glass of fluorescent lamps decontaminated by mercury, with calcium carbonate as a foaming agent, seeking the development and characterization of glass foams. The process variables investigated were: percentage of foaming agent (2, 3, 4 and 8 %), compaction pressure (20, 30 and 40 MPa); burning temperature (700, 750, 800 and 850 °C); heating rate (2.5, 5.0 and 7.5 °C∙min-1) and the glass size (11.0, 29. 0 and 91.0 μm). The following properties were monitored: density, porosity, mechanical strength and thermal conductivity. The results highlighted were the combination of burning temperature and percentage of foaming agent in determining the volumetric expansion, while the variable conformation pressure has unrepresentative influence. The best result obtained for burning temperature was at 800 °C in which the content of 3 % of CaCO3 showed expansion around 600 %. Decreases in glass size and increases in heating rate induced decreases in expansion. The results showed that all glass foams obtained in this study have density (0.187 to 0.282 g∙cm-3) compatible with commercial products. The maximum mechanical strength obtained was 0.75 MPa also compatible with commercial glass foams. The thermal conductivity showed a value of 0.03 W∙m-1 ∙°C1 at 150 °C, which characterizes the glass foams prepared with 3% of CaCO3 as a thermal insulator. Regarding the analysis of the presence of metals, the preparation of glass foams is presented as an alternative to the disposal of fluorescent lamps glasses, with a reduction of 97.8 % in the emission of lead, in comparison to the emission observed in the decontaminate glass.
Espumas vítreas são materiais heterofásicos empregados para isolamento acústico e térmico e, comparadas a outros materiais, são leves e resistentes. As espumas vítreas podem ser preparadas a partir de vidros de embalagens, de tubos de raios catódicos e de outros resíduos como cinzas volantes. Resíduos de lâmpadas fluorescentes, classificados pela NBR 10.004-04 como perigosos devido à presença de mercúrio, têm características para serem utilizados na obtenção de espumas vítreas. A descontaminação deste resíduo torna possível seu envio para aterros controlados, no entanto faz-se necessário o desenvolvimento de processos que contemplem a utilização destes em produtos de interesse econômico, considerando o aspecto ambiental envolvido. Desta forma, este trabalho tem como objetivo preparar corpos cerâmicos a partir de vidro de lâmpadas fluorescentes descontaminado de mercúrio, com carbonato de cálcio como agente espumante, buscando o desenvolvimento e a caracterização de espumas vítreas. As variáveis processuais investigadas foram: percentual de agente espumante (2, 3, 4 e 8%); pressão de conformação (20, 30 e 40 MPa); temperatura de queima (700, 750, 800 e 850°C); taxa de aquecimento (2,5, 5,0 e 7,5 °C∙min-1) e granulometria do vidro (11,0, 29,0 e 91,0 μm). Foram monitoradas as seguintes propriedades: massa específica, porosidade, resistência mecânica e condutividade térmica. Destacam-se como resultados a combinação dos fatores temperatura de queima e percentual de agente espumante na determinação da expansão volumétrica, enquanto que a variável pressão de conformação não possui influência representativa. O melhor resultado obtido para temperatura de queima foi em 800°C no qual o teor de 3% de CaCO3 apresentou expansão de cerca de 600%. Diminuições na granulometria e aumentos na taxa de aquecimento induzem a diminuições na expansão. Os resultados mostram que todas as espumas vítreas obtidas neste estudo possuem massa específica (0,187– 0,282 g∙cm-3) compatíveis com produtos comerciais. A resistência mecânica máxima obtida foi de 0,75 MPa também compatível com espumas vítreas comerciais. A condutividade térmica apresentou o valor de 0,03 W∙m-1 ∙°C-1, em 150°C, o que caracteriza as espumas vítreas, preparadas com 3% de CaCO3, como isolante térmico. Em relação à análise da presença de metais, a preparação de espumas vítreas se apresentou como uma alternativa para o emprego de vidros de lâmpadas fluorescentes, com diminuição de até 98,7% da quantidade de chumbo solubilizado, em comparação ao chumbo solubilizado do vidro descontaminado
Keywords: Resíduos perigosos; Lâmpadas fluorescentes; Materiais - Testes; Hazardous wastes; Fluorescent lamps; Materials - Testing